Analisis Peran Guru Dalam Membangun Kepercayaan Diri Siswa Pada Tema 3 Subtema 3 Pembelajaran 2 kelas III SD Negeri Pedurungan Kidul 02 Semarang - Cahyani, Septi Dwi; Mudzanatun, Mudzanatun; Subekti, Ervina Eka (STKIP Andi Matappa Pangkep, 2021)
This research aimed to determine the extent to which the teacher's role in building students’ confidence in theme 3 sub-theme 3 learning 2 class III SD Negeri Pedurungan Kidul 02 Semarang. The method of this research was a qualitative approach to descriptive research. The data collection techniques of this research were observation, interviews, questionnaires, and documentation. The data analysis technique used the Miles and Huberman stages which were carried out by means of technical triangulation. The results showed that in building students’ self-confidence, the teacher's role was very influential. Teachers as the role model in the school can give a lot of impact to build students’ self-confidence. There are some ways to build student self-confidence, such as understanding, modeling, habituation, motivations in learning, building student self-confidence starting from directing and guiding students according to the student's circumstances.